2009
DOI: 10.1111/j.1365-3121.2009.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

North Arch volcanic fields near Hawaii are evidence favouring the restite‐root hypothesis for the origin of hotspot swells

Abstract: A pronounced regional bathymetric swell is a common feature of oceanic hotspot volcanism. Recently, the hypothesis of a buoyant sublithospheric swell-root has been favoured, the root being either a Ôrefracted plumeÕ of hot, buoyant and hence lowviscosity plume material embedded within surrounding higher viscosity asthenosphere, or a Ôrestite-rootÕ composed of hot and more viscous residues to hotspot melt-extraction from the hottest central portion of the upwelling plume. In this article, we present numerical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Although constraining the impact of a hot spot influence on the lithosphere is important for our understanding of the lithosphere and hot spot‐lithosphere dynamics, the effects of plume‐lithosphere interaction on LAB depth are not well known globally. It has been hypothesized that the plume may locally decrease [ Li et al , 2004] or increase [ Hall and Kincaid , 2003; Yamamoto and Morgan , 2009] lithospheric thickness. Therefore, the implications of these results for “normal” lithosphere are not clear, and we continue, focusing on receiver function results from other regions.…”
Section: Previous Resultsmentioning
confidence: 99%
“…Although constraining the impact of a hot spot influence on the lithosphere is important for our understanding of the lithosphere and hot spot‐lithosphere dynamics, the effects of plume‐lithosphere interaction on LAB depth are not well known globally. It has been hypothesized that the plume may locally decrease [ Li et al , 2004] or increase [ Hall and Kincaid , 2003; Yamamoto and Morgan , 2009] lithospheric thickness. Therefore, the implications of these results for “normal” lithosphere are not clear, and we continue, focusing on receiver function results from other regions.…”
Section: Previous Resultsmentioning
confidence: 99%
“…More likely, episodes of increased thermal plume anomalies explain the observed lithospheric thickness variations. Periods of increased plume temperatures or flux could cause increased melting depths that are reflected in thicker regions of depletion and dehydration, and also thicker tectonic plates (Ito, ; Yamamoto & Morgan, ). Alternatively, propagation of small scale convective instabilities could periodically increase upwelling (Martinez & Hey, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Sp receiver‐function study by Rychert et al () identifies a velocity interface at 100–150‐km depth that they identify with the onset of melting as the hot plume rises through the pressure‐dependent solidus. In geodynamical modeling, the idealized plume models of Ribe and Christensen (, ) and Yamamoto and Morgan () can explain many features of Hawaiian swell bathymetry and island volcanism. Later studies of plume bathymetry have confirmed the general consistency of the plume model in terms of buoyancy flux and dynamic topography (Crosby & McKenzie, ; King & Adam, ; Wessel, ).…”
Section: Paradigm Shootout: Plume Plutonism Versus Metasomatismmentioning
confidence: 99%
“…Diffuse magmatic infiltration that extends laterally for hundreds of kilometers across the Hawaiian hot spot swell would raise the temperature of the lithosphere toward its solidus, in conflict with seismic tomography of the swell region (e.g., Laske et al, ). In addition, it seems difficult to reconcile broad and diffuse magma ascent beneath the Hawaiian swell with the localized eruption of the North Arch basalts on the swell, as described by Yamamoto and Morgan ().…”
Section: Paradigm Shootout: Plume Plutonism Versus Metasomatismmentioning
confidence: 99%